PENGKAYAAN SUMBERDAYA IKAN DENGAN FISH APARTMENT DI PERAIRAN BANGSRING, BANYUWANGI - Kamaali, Muhammad Wildy; Baskoro, Mulyono S; Wisudo, Sugeng Hari (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The use of fishing gear which is not enviromentally can involve aquatic ecosystems damage where is, mainly for fish habitats damage such as coral reefs. Damaged coral reefs resulting in captures reduced, fish captures decrease, and the loss of some fish species on that water region, especially reef fishes. This fish apartment development and determine the direct impact to the Bangsring fisherman. Determining teh abudance and diversity of fish species as an indicator in the Bangsring waters. Analyze the success level of fish apartment in enrichment of fish stoks and improve fish babitats in Bangsring, Banyuwangi. Fish apartment cultivation on Bangsring waters could restore the enrichment of fish resources, seen from the accretion of fish species, the increasing of fish captured up to 100%, capture distance that near, and efficient at the time of capturing. Fish apartment could restore aquatic ecosystems damaged, especially on Bangsring waters.